Resolved but Not Forgotten: The Effect of Resolved Placenta Previa on Labor Management - Feldman, Kristina M.; Robinson, Andre; Gellman, Caroline; Kaplowitz, Elianna; Hussain, Farrah N.; AL-Ibraheemi, Zainab; Strauss, Tirtza S.; Ashmead, Graham; Cole, David; Brustman, Lois (American Journal of Perinatology, 2022)
Objectives Placenta previa is diagnosed in up to 15% of pregnancies at the anatomy ultrasound and 0.5% persist to term. There is limited data regarding pregnancy outcomes with resolved previa. We aimed to examine patients with resolved placenta previa to determine if abnormal placentation at any time during pregnancy is associated with adverse events during labor.Study Design Patients with placenta previa were identified after second trimester ultrasound, included if placenta previa resolved with the placental edge greater than 2 cm from the internal cervical os, and excluded if placenta previa persisted to term, resolution occurred prior to 20 weeks, patients underwent a prior cesarean delivery, or delivered at an outside institution. Time-matched controls were identified among patients with normal placental location. Demographic data and outcomes were collected. Student's t-test, Wilcoxon's rank-sum test, Chi-square, Fisher's exact test, and univariable and multivariable logistic regression were used as appropriateResults Overall, 560 patients had placenta previa, 275 had resolved placenta previa, 285 were excluded. Resolved placenta previa patients were significantly older with lower prepregnancy body mass index (BMI), were significantly more likely to be a current smoker, have used assisted reproductive technology, and have had previous uterine surgeries. Overall, 10.2% of patients with resolved placenta previa experienced postpartum hemorrhage, compared with 2.1% in the normal placentation group. Patients with resolved placenta previa were 5.2 times more likely to have a postpartum hemorrhage (odds ratio [OR] = 5.2, 95% confidence interval [CI]: 2.1–12.7; p < 0.01) and 3.4 times more likely to require extra uterotonic medications (OR = 3.4, 95% CI: 1.9–6.2; p < 0.01). There is no difference with regard to rates of operative delivery for fetal distress (OR = 1.2, 95% CI: 0.7–1.9; p = 0.48), or category-II or-III fetal heart tracing around the time of delivery.Conclusion Patients with resolved placenta previa had a higher rate of postpartum hemorrhage and use of uterotonic agents. This information might have important clinical implications and could be incorporated into the hemorrhage risk assessment during labor.Key Points
Keywords: placenta previa; resolved placenta previa; anatomy ultrasound; postpartum hemorrhage; uterotonic medication; fetal distress; expedited delivery